Diversifying agribusiness systems through maize forage feed innovations - International Livestock Research Institute (2024)
The CGIAR Research Initiative on Diversification in East and Southern Africa (Ukama Ustawi) Initiative aims to help smallholders transition to sustainably intensified, diversified, and de-risked agri-food systems based on maize in 12 East and Southern African countries. Specifically, it seeks to enable 50,000 value chain actors, including farmers (at least 40% women, 40% youth), to adopt climate-smart maize-based intensification and diversification practices and one million to access digital agro-advisory services. This video explains how diversifying agribusiness systems through maize forage feed innovations is helping smallholders in Africa.